A β‐Diketiminate‐Stabilized Sila‐Acyl Chloride: Systematic Access to Base‐Stabilized Silicon Analogues of Classical Carbonyl Compounds. (21st September 2018) - Do, Dinh Cao Huan; Protchenko, Andrey V.; Ángeles Fuentes, M.; Hicks, Jamie; Kolychev, Eugene L.; Vasko, Petra; Aldridge, Simon
Abstract: An oxidation/substitution strategy for the synthesis of silicon analogues of classical organic carbonyl compounds is reported, by making use of a novel β‐diketiminate‐supported sila‐acyl chloride—the first example of such a compound isolated without the use of a stabilizing Lewis acid. Nucleophilic substitution at the Si IV center allows direct access to the corresponding sila‐aldehyde and sila‐ester. An alternative approach utilizing the reverse order of synthetic steps is thwarted by the facile rearrangement of the corresponding Si II systems featuring either H or OR substituents. As such, the isolation of (N‐nacnac)Si(O)Cl represents a key step forward in enabling the synthesis of sila‐carbonyl compounds by a synthetic approach ubiquitous in organic chemistry.